Static-dynamic stability of gymnasts’ bodies on the rings apparatus - HAKMAN, A.; LYTVYNENKO, YURII; TOMICH, LILIYA; LAZAKOVYCH, YULIIA; MARTYNIUK, OKSANA; CHEREDNICHENKO, SERHIY; HRDZELIDZE, SERHII; MARTYN, PETRO (Journal of Physical Education and Sport ® (JPES), 2026)
The aim of the study was to investigate the rational mechanisms of static-dynamic stability of the body of gymnasts of different skill levels when performing exercises on the rings apparatus. Materials and methods. Seventeen qualified athletes (I sports category) and ten highly qualified athletes (Honored Masters of Sport, International Masters of Sport) participated in a 4-week descriptive experiment. The study examined the characteristics of performing a large backward rotation on the rings apparatus by athletes of different skill levels. Each athlete performed three attempts, with a 5-minute rest period between attempts. The athletes' movements were recorded using the “Contemplas” mobile video recording and analysis system with a resolution of 150 frames per second, followed by quantitative and qualitative biomechanical analysis and statistical data processing. The kinematic indicators of the gymnasts' movement technique were used to study the mechanisms of posture regulation as a component of the body's static-dynamic stability. As an integral indicator of the gymnast's body statodynamic stability during the backward giant swing, the oscillation of the rings in the sagittal plane was recorded in the final phase of the movement. Results. The static-dynamic stability of an athlete should be considered as a multifactorial phenomenon that takes into account the specifics of the conditions for the implementation of programmed sports movements, while identifying effective mechanisms for regulating body posture with the subsequent development of methodologies, techniques, individual training programs, etc. The results of the study show that a rational mechanism ofstatic-dynamic stability of a gymnast's body is one in which there is a balance of forces acting on his body on both sides of the conditional vertical when performing a descent and ascent (ensuring the symmetry of the trajectory of the athlete's body center of mass), as a result, there is no horizontal swaying of the rings in the handstand after performing large turns on the rings (oscillations do not exceed 0.05-0.07 m); a prerequisite for this is the movements of open and closed kinetic chains, which are implemented as an integral and coordinated mechanism under the leading role of the connecting links of the body – the pelvis and lumbar spine, which transmit and coordinate mechanical impulses in conditions of constant change in the interaction of the athlete's body kinematic chains and the state of support. Conclusions. Thus, in conditions of mobile support, the stability of the athlete's body is largely determined by the stability of the lumbar-pelvic complex, which plays an important role in ensuring the balance of the whole body. At the same time, the lumbosacral complex should be considered as a part of the body that includes the lower torso and pelvis, which actively interact with the upper torso and thighs.
Keywords: balance, rational mechanisms, sports gymnastics, rings exercises, technology.